Twelve-Month Results From the First-in-China Prospective, Multi-Center, Randomized, Controlled Study of the FREEWAY Paclitaxel-Coated Balloon for Femoropopliteal Treatment - Zhang, Bihui; Yang, Min; He, Tao; Li, Xuan; Gu, Jianping; Zhang, Xiaoming; Dai, Xiangchen; Li, Xuedong; Lu, Xinwu; Lang, Dehai; Hu, Hongyao; Chen, Xueming; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Several paclitaxel-coated balloons have been proved to provide better efficacy results than uncoated balloons in femoropopliteal lesions. But the efficacy and safety of FREEWAY balloons have not been investigated in Chinese patients. This study aimed to evaluate the efficacy and safety performance of FREEWAY paclitaxel-coated balloons versus uncoated balloons in Chinese femoropopliteal artery lesions. Methods: In this prospective multi-center randomized controlled FREEWAY-CHINA study, 311 patients with symptomatic lower limb ischemia (Rutherford category 2–5) and femoropopliteal lesions of 14 Chinese centers were randomly assigned in a 1:1 ratio to endovascular treatment with either FREEWAY paclitaxel-coated balloons or uncoated balloons (control). The primary endpoint was the 6-month clinically-driven target lesion revascularization (CD-TLR) rate. Second endpoints included the device and technical success rate, the ankle-brachial indexes (ABIs), Rutherford category change, the 6-month primary, the secondary patency rates, severe adverse effects, and the 12-month CD-TLR rate. Results: The two groups were comparable in terms of their demographic and lesion characteristics. Patients’ mean age was 70 years, and 70% were men. The mean lesion length was 71 mm. The 6-month CD-TLR rate was 2.6% in the FREEWAY group and 11.7% in the control group (P = .001). The 12-month CD-TLR rate was 2.7% in the FREEWAY group and 13.2% in the control group (P = .0005). Other endpoints, including patency rates, severe adverse effects, and ABI or Rutherford change, did not differ between the two groups. Conclusion: The FREEWAY balloon resulted in an effective decrease in CD-TLR rates and had similar safety results compared to the uncoated balloon in Chinese femoropopliteal artery patients at the 12-month follow-up appointment.